Hubungan Derajat Merokok dan Aktifitas Fisik pada Masa Covid-19 dengan Tekanan Darah dan Kejadian Hipertensi di Kota Palangkaraya: The Relationship Between Smoking Degrees and Physical Activity in the Time of Covid-19 with Blood Pressure and Hypertension Incidence in Palangka Raya City - Abi Bakring Balyas; Galih Indra Permana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Hypertension is a disease which there an increase in systolic and diastolic blood pressure of more than 140 mmHg and 90 mmHg (normal). This study aims to prove the relationship between physical activity and the degree of smoking with systolic and diastolic blood pressure. The research method used was a cross-sectional design with a total sample of 51 non-obese adult men. Sample selection using purposive technique. Physical activity was obtained by filling out the IPAQ (International Physical Activity Questionnaire. The degree of smoking obtained was measured using the Brinkman Index. The results showed that there was a significant relationship between the brinkman smoking index and systolic blood pressure and diastolic blood pressure and between physical activity and systolic blood pressure but not There is a significant relationship between physical activity and diastolic blood pressure.